Mathematical Modelling In Addiction Cases Online Games Using The SEIRS Model In Middle School Sivaliputta - Setiawan, Novyanto; Prihandono, Bayu; Pasaribu, Meliana (JOSTECH Journal of Science and Technology, 2024)
Online game addiction is a mental illness caused by the habit of playing online games for too long. The average duration of time a person is said to fall into the category of addiction to playing online games is if the duration of time spent is 20-25 hours per week. This research uses the SEIR model, Susceptible (S) is the subpopulation who has online games on their gadgets and plays online games for less than one hour/day, Exposed (E) is the subpopulation who plays online games for one to three hours/day, Infected (I) is the subpopulation who plays online games for more than three hours/day and Recovered (R) is the subpopulation who has stopped playing online games and does not have online games on their gadget. Mathematical models need to be searched and formed using the SEIR model. The research data used data obtained from the activities of Sivaliputta Junior High School students in playing online games.. The steps of this research began by determining the problem of online game addiction in the student population at Sivaliputta Junior High School, making assumptions and identifying variables (susceptible, exposed, infrcted, recovery), forming a mathematical model, determining the equilibrium point, determining basic reproduction value  and perform numerical simulations. The solution point will stabilize be asymptotically stable for a certain period of time with a susceptible population of 13 people, an exposed population of 61 people, an infected population of 46 people and a recovered population of 211 people.